Satellite Derived Water Quality Observations Are Related to River Discharge and Nitrogen Loads in Pensacola Bay, Florida - Lehrter, John C.; Le, Chengfeng (Frontiers in Marine Science, 2017)
Relationships between satellite-derived water quality variables and river discharges, concentrations and loads of nutrients, organic carbon, and sediments were investigated over a nine-year period (2003-2011) in Pensacola Bay, Florida, USA. These analyses were conducted to better understand which river forcing factors were the primary drivers of estuarine variability in several water quality variables. Remote sensing reflectance time-series data were retrieved from the MEdium Resolution Imaging Spectrometer (MERIS) and used to calculate monthly and annual estuarine time-series of chlorophyll a (Chla), colored dissolved organic matter (CDOM), and total suspended sediments (TSS). Monthly MERIS Chla varied from 2.0 mg m-3 in the lower region of the bay to 17.2 mg m-3 in the upper bay. MERIS CDOM and TSS exhibited similar patterns with ranges of 0.51 to 2.67 (m-1) and 0.11 to 8.9 (g m-3). Variations in the MERIS-derived monthly and annual Chla, CDOM, and TSS time-series were significantly related to monthly and annual river discharge and loads of nitrogen, organic carbon, and suspended sediments from the Escambia and Yellow rivers. Relationships differed, though, with monthly MERIS Chla most strongly correlated with river discharge lagged one-month, while monthly MERIS CDOM and TSS were most correlated with concurrent month river nitrate (NO3-) loads. Multiple regression models based on river loads (independent variables) and MERIS Chla, CDOM, or TSS (dependent variables) explained significant fractions of the variability (up to 62%) at monthly and annual scales. The most significant independent variables in the regressions were river nitrogen loads, which were associated with increased MERIS Chla, CDOM, and TSS concentrations, and river suspended sediment loads, which were associated with decreased concentrations. In contrast, MERIS water quality variations were not significantly related to river total phosphorus loads. The spatially synoptic, nine-year satellite record expanded upon the spatial extent of past field studies to reveal previously unseen system-wide responses to river discharge and loading variation. The results indicated that variations in Pensacola Bay Chla, CDOM, and TSS were primarily associated with riverine nitrogen loads. Thus, reducing these loads may improve water quality issues associated with eutrophication, turbidity, and water clarity in this system.